Phytochemical Synergy and Antioxidant Enzyme Activity of Azadirachta indica and Triticum aestivum Extracts - Qasim, Aniqa; Abbas, Khizir; Noor Ul Huda; Amir, Mariam (Indus Journal of Bioscience Research, 2025)
Rising demand for herbal products for therapeutic applications has driven the examination of synergistic effects between medicinally plants and nutraceutical plants. Azadirachta indica (Neem) is known for its numerous phytochemicals such as flavonoids, alkaloids, terpenoids and phenolics that display strong antimicrobial, anti-inflammatory and antioxidant properties. Likewise, Triticum aestivum (Wheatgrass) has been reputed for containing chlorophyll, amino acids, vitamins, and phenolic compounds, some of which involved in detoxification, immuno-modulation, and anti-oxidant activity. The current study is aimed at understanding synergistic interactions between Neem and Wheatgrass extracts in context to qualitative and quantitative phytochemical profiling and antioxidant enzyme activities. Bioactive components were determined using standard phytochemical screening methods, while quantitative determination of proteins and phenolics were done. Enzymatic anti-oxidant assays for catalase, peroxidase and superoxide dismutase were carried out to check oxidative defense capability of extracts both separately and in combination. The results showed that combined extracts possessed a higher antioxidant enzymatic activity compared to non-combined arrangements, which indicated that bioactive compounds were potentiating each other. The present investigation emphasizes the potential use of polyherbal formulations for enhancing the antioxidant defense and endorses the traditional as well as modern use of Neem and Wheatgrass for nutraceutical as well as therapeutic preparations.